TGF-β and CTGF are Mitogenic Output Mediators of Wnt/β-Catenin Signaling in Desmoid Fibromatosis. Issue 8 (September 2017) - Varghese, Sumi; Braggio, Danielle A.; Gillespie, Jessica; Toland, Amanda E.; Pollock, Raphael; Mayerson, Joel; Scharschmidt, Thomas; Iwenofu, Obiajulu H.
Abstract : Desmoid fibromatosis is a locally aggressive clonal fibroblastic proliferation with high recurrence rates and no metastatic potential. Implicated molecular aberrations occur within the Wnt/β-catenin pathway ( APC and β-catenin gene mutations). Transforming growth factor-β (TGF-β) and connective tissue growth factor (CTGF) are profibrotic growth factors, downstream from nuclear translocation of β-catenin, that lead to increased fibrogenesis. CTGF (a downstream effector of TGF-β) is a matricellular protein that modulates the activity of growth factors, adhesion molecules, integrins, and extracellular matrix thus playing a central role in tissue remodeling and fibrosis. Recently there has been growing interest in use of extracellular matrix inhibitors for treatment of various fibrogenic diseases. Desmoid fibromatosis samples (n=15) were evaluated for expression of β-catenin, TGF-β, and CTGF using immunohistochemistry on formalin paraffin-embedded material. A control group comprising scar tissue and adjacent normal skin (n=10) were simultaneously immunostained with above mentioned markers. Real-time polymerase chain reaction was performed on frozen specimens of desmoid fibromatosis (n=6) and normal skin (n=2). All 15 desmoid tumors were positive for β-catenin (surrogate marker of Wnt/β-catenin pathway dysregulation) which was negative in control normal skin and scar samples. TGF-β and CTGF were negative in 9 of 10 normal skin controls. TGF-β and CTGF were positive in all cases of scar tissue. All 15 cases of desmoid tumors were positive for TGF-β and CTGF. The real-time polymerase chain reaction showed higher expression levels of TGF-β and CTGF in desmoid fibromatosis compared with normal skin. The high constitutive expression of β-catenin downstream effectors; TGF-β, CTGF has the potential for enabling targeted therapy.